Effectiveness of Short Foot Exercises Versus Towel Curl Exercises to Improve Balance and Foot Posture in Individuals with Flexible Flat Foot - Sayali N. Pisal1 , Khushboo Chotai2 , Smita Patil2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Flexible flat foot is a condition of foot in which the medial longitudinal arch is lowered which is visible in weight bearing foot. This condition may be asymptomatic and needs to be treated to prevent further overuse injuries. Many of the literature suggest that individuals with flexible flat foot shows imbalances in the strength of IFM like abductor hallucis, flexor hallucis brevis, flexor digitorum brevis and interosseous muscles which plays major role in maintaining stability. The dynamic balance is found to be more affected in flexible flat foot which needs to be treated by strengthening the IFM. Strengthening IFM with greater efficacy can improve the dynamic balance and also have impact on foot posture of individuals with flexible flat foot. Objective: to find the effect of 2 different types of IFM strengthening on dynamic balance Material and Method: In this pre-post intervention study 40 individuals with flexible flat foot were included. They were randomly divided into 2 groups with 20 individuals in each group. Group A was instructed to perform short foot exercises and Group B was instructed to perform towel curl exercise for four weeks. After pre-post assessment, data was analysed with help of appropriate statistical methods. Results: According to result the in Group A and Group B there is significant increase in both right and left anterior, posteromedial and posterolateral directions with p value < 0.0001. Conclusion: Both short foot exercise and towel curl exercise are found to be equally effective in improving the dynamic balance in individuals with flexible flat foot. The impact of these exercises on foot posture needs to be taken into consideration.